2020
DOI: 10.1584/jpestics.d19-072
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature on the dissipation of total- and water-extractable pesticides in Japanese soils

Abstract: We investigated the dissipation of 27 pesticides in five Japanese soils at three temperatures and the variability of activation energies (E a). The dissipation of total pesticides extracted sequentially using water and acetone was fitted to a single first-order (SFO) model. The E a values calculated from the dissipation rate constants of the SFO model showed a normal distribution with a median of 61.1 kJ mol −1. The dissipation of water-extractable pesticides (i.e., phytoavailable pesticides) was fitted to a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Ok et al 28) reported that the DT 50 s of butachlor and pyrazosulfuron-ethyl in paddy water tested in the summer crop season were faster than those tested in the summer. Meanwhile, Motoki and Iwafune 29) found that the time-dependent increase in K d of flutolanil became higher as the incubation temperature increased. In 2012 and 2014, the average water temperatures in paddy fields were 2.5-6.0°C higher than those in the lysimeters, whereas the average water temperatures in both the lysimeters and paddy fields were similar in 2015 (see Supplemental Table S6).…”
Section: Factors Affecting Experimental Performance Of Lysimeters Andmentioning
confidence: 99%
“…Ok et al 28) reported that the DT 50 s of butachlor and pyrazosulfuron-ethyl in paddy water tested in the summer crop season were faster than those tested in the summer. Meanwhile, Motoki and Iwafune 29) found that the time-dependent increase in K d of flutolanil became higher as the incubation temperature increased. In 2012 and 2014, the average water temperatures in paddy fields were 2.5-6.0°C higher than those in the lysimeters, whereas the average water temperatures in both the lysimeters and paddy fields were similar in 2015 (see Supplemental Table S6).…”
Section: Factors Affecting Experimental Performance Of Lysimeters Andmentioning
confidence: 99%
“…The daily mean temperatures during the period of 42 days after pesticide application were 27 and 23 °C for EX-1 and EX-2, respectively. Because the dissipation rates of pesticides increase with temperature, 42,43 the temperature was not the main factor responsible for the annual variation of the dissipation rates of THI and FOS in the soil. However, the mean moisture contents of soil samples (0−10 cm depth) during the 42 day period were 42% and 50% of WHC for EX-1 and EX-2, respectively; thus, the high-soil moisture conditions may have accelerated the dissipation of pesticides in soil as previously reported.…”
Section: Pot Experimentsmentioning
confidence: 99%
“…These results support the link between temperature, HRT, and pesticide behavior. Higher temperatures enhance the microbial activity behind the biotransformation and are accompanied by important solar radiations, which favors photolysis (Kaur and Vishnu, 2022;Law et al, 2014;Motoki et al, 2020;Rani and Sud, 2015). Therefore, significant pesticide transformation was noticed during periods of high temperature.…”
Section: Dissipation Efficiency and Pond Propertiesmentioning
confidence: 99%